KEKERABATAN BAHASA AKIT DAN DUANU: KAJIAN LEKSIKOSTATISTIK - Zainal Abidin (Balai Bahasa Provinsi Riau, 2014)
This study aims to find the kindship relation between Akit language and Duanu language in Riau Province. Data was in the form of Swadesh vocabulary list of eight regional languages Akit observations areas of Akit Language and Duanu language users in Riau Province that was collected using documentation technique and analyzed by applying quantitative descriptive method that followed the steps of transcribing, classifying, comparing, and formulating the research results. Analyzing data was carried out by using lexicostatistics technique. The results that obtained from the research are Akit language and Duanu language are in one family group of language (36-81%) . The proximity of APN language and language DSL has a very high closeness (53,5%) Akit Language in Kepulauan Meranti is the same language as Akit language in Hutan Panjang, Bengkalis. Language that is the closest to the farthest with the two languages consecutively as the following APN and DPP language (52,75%), APN and DTP language (51,75%), APN and DSL had the same percentage as APN and DBL (51,5%), ASS and DPP language (51,25%), ASN and DSL language (50,75%),ASS and DSL language (46,5%), AHP and DPP language (44%), ASS and DBL language and ASN and DBL language (42,5%), AHP and DSL language (42%), AHP and DTP (39,5%), AHP and DBL (37%). Penelitian ini bertujuan menemukan hubungan kekerabatan antara bahasa Akit dan Duanu di Provinsi Riau. Data berupa daftar Swades dari delapan daerah pengamatan bahasa Akit dan Duanu di Provinsi Riau dikumpulkan dengan teknik dokumentasi kemudian dianalisis dengan metode deskriptif kuantitatif mengikuti langkah-langkah mentranskripsikan, mengklasifikasikan, membandingkan, dan merumuskan hasil penelitian. Penganalisisan dilakukan dengan teknik leksikostatistik.Hasil yang diperoleh adalah bahasa Akit dan Duanu, dapat ketahui bahwa kedua bahasa tersebut berada dalam satu keluarga (36─81%). Kedekatan bahasa APN dan bahasa DSL memiliki kedekatan yang sangat tinggi (53,5%). Bahasa Akit Sonde di Kepulauan Meranti merupakan bahasa yang sama dengan Akit Hutan Panjang di Bengkalis. Bahasa yang terdekat sampai dengan terjauh dengan dua bahasa tersebut berturutturut yaitu bahasa ASS dan DTP (52,75%), bahasa APN dan DTP (51,75%), bahasa APN dan DPP dan APN dan DBL (51,5%), bahasa ASS dan DPP (51,25%), ASN dan DSL (50,75%), ASS dan DSL (46,5%), AHP dan DPP (44%), ASS dan DBL dan ASN dan DBL (42,5%), AHP dan DSL (42%), ASN dan DTP (40%), AHP dan DTP (39,5%), AHP dan DBL (37%).